Education Leadership in the Era of Digital Transformation and Artificial Intelligence: Implications for Sustainable Human Development - Natalina Damayanthi; Ardin Sianipar; Widya Angelia (Universitas Pelita Harapan, 2026)
This study examines how educational leadership responds to digital transformation and artificial intelligence (AI), and how such leadership fosters sustainable human development in Indonesia and similar developing contexts. Methodology, A systematic literature review (SLR) was conducted using PRISMA 2020 guidelines. Fifteen eligible articles published between 2018 and 2024 were analyzed through a thematic synthesis and bibliometric mapping approach, with quality appraisal guided by the Joanna Briggs Institute (JBI) standards. The results show that digital leadership improves instructional quality, organizational innovation, and governance efficiency. AI in education enables data-driven decision-making, but it also raises concerns about equity and ethics. In resource-constrained settings, leadership that strikes a balance between technological use and humanistic values makes a significant contribution to human development. The study focuses solely on peer-reviewed articles from 2018 to 2024, potentially excluding gray literature and earlier foundational work. The findings emphasize the urgency of strengthening digital leadership capacity, developing AI governance in education, and ensuring inclusive access to technology. This study integrates leadership, digital transformation, AI, and human development into a unified framework, offering fresh insights for policy and practice.